Monte Carlo simulated corrections for beam commissioning measurements with circular and MLC shaped fields on the CyberKnife M6 System: a study including diode, microchamber, point scintillator, and synthetic microdiamond detectors. (16th January 2017) - Francescon, P; Kilby, W; Noll, J M; Masi, L; Satariano, N; Russo, S
Abstract: Monte Carlo simulation was used to calculate correction factors for output factor (OF), percentage depth-dose (PDD), and off-axis ratio (OAR) measurements with the CyberKnife M6 System. These include the first such data for the InCise MLC. Simulated detectors include diodes, air-filled microchambers, a synthetic microdiamond detector, and point scintillator. Individual perturbation factors were also evaluated. OF corrections show similar trends to previous studies. With a 5 mm fixed collimator the diode correction to convert a measured OF to the corresponding point dose ratio varies between −6.1% and −3.5% for the diode models evaluated, while in a 7.6 mm × 7.7 mm MLC field these are −4.5% to −1.8%. The corresponding microchamber corrections are +9.9% to +10.7% and +3.5% to +4.0%. The microdiamond corrections have a maximum of −1.4% for the 7.5 mm and 10 mm collimators. The scintillator corrections are <1% in all beams. Measured OF showed uncorrected inter-detector differences >15%, reducing to <3% after correction. PDD corrections at d > d max were <2% for all detectors except IBA Razor where a maximum 4% correction was observed at 300 mm depth. OAR corrections were smaller inside the field than outside. At the beam edge microchamber OAR corrections were up to 15%, mainly caused by density perturbations, which blurs the measured penumbra. With larger beams and depths, PTW and IBA diode corrections outside the beam were up to 20% while the Edge detector needed smaller corrections although these did vary with orientation. These effects are most noticeable for large field size and depth, where they are dominated by fluence and stopping power perturbations. The microdiamond OAR corrections were <3% outside the beam. This paper provides OF corrections that can be used for commissioning new CyberKnife M6 Systems and retrospectively checking estimated corrections used previously. We recommend the PDD and OAR corrections are used to guide detector selection and inform the evaluation of results rather than to explicitly correct measurements.